2014
DOI: 10.3390/cells3020546
|View full text |Cite
|
Sign up to set email alerts
|

Role of Ubiquitylation in Controlling Suppressor of Cytokine Signalling 3 (SOCS3) Function and Expression

Abstract: The realisation that unregulated activation of the Janus kinase–signal transducer and activator of transcription (JAK–STAT) pathway is a key driver of a wide range of diseases has identified its components as targets for therapeutic intervention by small molecule inhibitors and biologicals. In this review, we discuss JAK-STAT signalling pathway inhibition by the inducible inhibitor “suppressor of cytokine signaling 3 (SOCS3), its role in diseases such as myeloproliferative disorders, and its function as part o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 72 publications
2
32
0
Order By: Relevance
“…In addition, Socs1 and Socs3 are known to function as part of a multi-subunit E3 ubiquitin ligase complex, and mark target proteins for proteasomal degradation. 39 , 40 Using immunoprecipitation assays, we found that both Socs1 and Socs3 could integrate Traf6 to form a complex. Moreover, ubiquitination of Traf6 was enhanced in cells overexpressing Socs1 or Socs3, resulting in the accelerated degradation of Traf6.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, Socs1 and Socs3 are known to function as part of a multi-subunit E3 ubiquitin ligase complex, and mark target proteins for proteasomal degradation. 39 , 40 Using immunoprecipitation assays, we found that both Socs1 and Socs3 could integrate Traf6 to form a complex. Moreover, ubiquitination of Traf6 was enhanced in cells overexpressing Socs1 or Socs3, resulting in the accelerated degradation of Traf6.…”
Section: Discussionmentioning
confidence: 96%
“…The ubiquitination reaction consists of the covalent attachment of ubiquitin (an 8-kDa polypeptide) to lysine residues in target proteins4041. Additionally, small ubiquitin-like modifier (SUMO) proteins 1, 2 and 3 can be covalently conjugated to specific lysine residues in target proteins by a process termed SUMOylation4243.…”
mentioning
confidence: 99%
“…Following their induction, STAT expression levels decline within 20-140 minutes additionally via ubiquitination. 26 SOCS3 is the predominant regulator. 27 Thus, activated STAT3, like PtdIns 3,4,5-P 3 , serves as a sensor which regulates its own activation.…”
Section: Discussionmentioning
confidence: 99%